2021
DOI: 10.1063/5.0054439
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of mononuclear Cu-based molecule from density-functional theory with self-interaction correction

Abstract: We investigate the electronic structure of a planar mononuclear Cu-based molecule [Cu(C6H4S2)2]z in two oxidation states (z = −2, −1) using density-functional theory (DFT) with Fermi–Löwdin orbital (FLO) self-interaction correction (SIC). The dianionic Cu-based molecule was proposed to be a promising qubit candidate. Self-interaction error within approximate DFT functionals renders severe delocalization of electron and spin densities arising from 3d orbitals. The FLO-SIC method relies on optimization of Fermi–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This can be resolved by using localized orbitals, but there are many possible localization schemes and the magnitude of the SIC will depend on the particular one selected. Recent development work has focused on Fermi‐Löwdin orbitals (FLO), 139,156–158 which provide a convenient framework for general application of the SIC to chemical systems of any size 159–163 . Ongoing development has involved orbital‐dependent scaling, 150,164 as well as use of FLOSIC with the density‐consistent effective potential 165,166 or the Krieger‐Li‐Iafrate 167,168 approximation to the optimized effective potential.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be resolved by using localized orbitals, but there are many possible localization schemes and the magnitude of the SIC will depend on the particular one selected. Recent development work has focused on Fermi‐Löwdin orbitals (FLO), 139,156–158 which provide a convenient framework for general application of the SIC to chemical systems of any size 159–163 . Ongoing development has involved orbital‐dependent scaling, 150,164 as well as use of FLOSIC with the density‐consistent effective potential 165,166 or the Krieger‐Li‐Iafrate 167,168 approximation to the optimized effective potential.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent development work has focused on Fermi-Löwdin orbitals (FLO), 139,[156][157][158] which provide a convenient framework for general application of the SIC to chemical systems of any size. [159][160][161][162][163] Ongoing development has involved orbital-dependent scaling, 150,164 as well as use of FLOSIC with the densityconsistent effective potential 165,166 or the Krieger-Li-Iafrate 167,168 approximation to the optimized effective potential.…”
Section: Self-interaction Correctionsmentioning
confidence: 99%
“…The 3d−σ, and 3d−σ–π active spaces each fail to predict the experimentally expected spin density, predicting about 90% of the unpaired electron on the Cu center. A previous study has suggested a large range between about 50 and 70% of spin density on the metal; ,, however, it is clear that these two active spaces predict a nearly completely localized spin on the copper center.…”
Section: Resultsmentioning
confidence: 80%
“…Computational studies of these complexes and their analogs are rather numerous, especially when considering DFT results. Metal dithiolates have long been studied as a paradigmatic case of ligand-noninnocent redox behavior, as well as consistent examples of strong metal–ligand covalency . In the context of the [Cu­(II)­(mnt)] 2 2– qubit candidate, the strong covalency has been linked to the relatively long vibrational relaxation times .…”
Section: Introductionmentioning
confidence: 99%
“…In a FLOSIC calculation, the FODs are optimized to produce FLOs corresponding to the minimum FLOSIC total energy. More details on obtaining FLOs can be found in previous publications , and in the work of Mishra et al…”
Section: Theory and Methodsmentioning
confidence: 99%